Symbolic violence, social media: A sociological analysis - Alrawashda, Maissa Nasser (Opción, 2020)
This article provides a sociological vision to explain how social media contributed to renewing and spreading the discourse of violence by using the Content Analysis approach. As a result, social interaction in the virtual space through social media applies the same principle of social interaction that occurs in the real society. In conclusion, academic and educational institutions set their sights on establishing the foundations of a societal culture based on the values of human rights and on the principles of equity and gender equality among their students.